Comparative histomorphological studies on the bronchioles of mithun (Bos frontalis) and zebu (Bos indieus) - KALITA, H C; BHATTACHARYYA, R (The Indian Journal of Animal Sciences, 2014)
A comparative study was carried out on the histomorphological features of the various segments of bronchioles in the lungs of mithun and zebu. The large bronchioles of mithun revealed a less folded mucosa and were supported by discontinuous muscularis mocosae, while the mucosa of zebu was more folded. The lamina epithelial is had pseudostratified ciliated columnar epithelium with few goblet cells. The number of ciliated columnar cells was reduced while that of the non ciliated short columnar 'clara' cells was increased towards the terminal bronchioles. The respiratory bronchioles were and 5-8 and 5-6 generations in mithun and zebu. The respiratory bronchioles revealed distinct with distended lumen in mithun. The epithelium of the respiratory bronchioles were shorter along with more number of cells in the inter-alveolar septia of zebu.